(untitled) (Лучшие интеллектуальные исследования, 2024)
Abstract:This article examines contemporary approaches to developing writing skills in English language teaching, highlighting the importance of writing for both students and educators. It discusses methods such as the Process writing approach, which emphasizes drafting and revising, and the Genre-Based Approach, which teaches students to adapt their writing to various contexts. Collaborative Writing is presented as a means to promote peer feedback and social learning, while writing workshops offer interactive spaces for students to share their work and receive constructive criticism. The article includes insights form notable figures such as Donald Murray, John Swales and Lev Vygotskiy, reinforcing the idea that effective writing instruction fosters clearer communication and prepares students for diverse writing tasks in academic and professional settings.